Pembelajaran dengan Google Classroom dalam Meningkatkan Hasil Belajar Sejarah - Lukmanulhakim, Cecep (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
Google Classroom's approach to learning is part of our strategy to use technology to facilitate the learning process for teachers and students. Through this Google Classroom, teachers can provide materials related to the subjects they teach. This is so that students can immediately see their grades, such as presenting materials, submitting assignments, and uploading student grades. Additionally, Google Classroom could be an alternative to replace late meetings when teachers are out of town or busy during class hours. The formulation of the problem in this study is as follows. How can using Google Classroom for online learning improve history learning outcomes? The research method used in this study is descriptive qualitative research related to problem-solving strategies. The reason for using this qualitative descriptive study is that the authors want to improve and enhance the quality of learning. Based on our findings: 1) On Basic Skills 3.7, 2 (5.6%) students had the lowest scores with values between 75 and 79, and 13 (36.1%) participants had the highest scores with values between 85 and 89; educate the 2) For baseline competency 3.8, 12 (33.3%) students had the lowest scores with values between 80 and 84, and 8 (22.2%) students had the highest scores with values between 90 and 94. 3) For Basic Competency 3.9, the lowest score with a value less than 75 is 1 (2.8%) student and the highest score with a value between 90 and 94 is 4  (11.1%) students. 4) For Baseline Competency 3.10, 3 (8.3%) students had the lowest score with a value less than 75 and 4 (11.1%) students had the highest score with a value between 95 and 100